Penggaruh Perusahaan Multinasional di Indonesia terhadap Sektor Ekonomi Lokal - Septina Rahmania; Shely Novitasari (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to examine the influence of multinational companies on the local economic sector in Indonesia. The method used is qualitative descriptive research with a literature study approach, which is based on the analysis of various secondary data sources such as scientific journals, policy reports, and economic documents. The results of the study indicate that the presence of multinational companies has a positive contribution to the local economy, including through improving state apparatus, modern technology transfer, job creation, and strengthening global production networks that can drive regional economic growth. However, this study also identified a number of negative impacts, such as dependence on foreign technology, low added value of local industry, and the emergence of social inequality and environmental damage. Therefore, a centralized and targeted policy is needed from the government to regulate the role of multinational companies so that the benefits obtained can be greater than the risks, especially in the context of sustainable economic development at the regional level.